Research Progress on the Antiviral Activity of Glycyrrhizin and its Derivatives in Liquorice - Huan, Changchao; Xu, Yao; Zhang, Wei; Guo, Tingting; Pan, Haochun; Gao, Song (Frontiers in Pharmacology, 2021)
Liquorice is a traditional medicine. Triterpenoids such as glycyrrhizin and glycyrrhetinic acid are the main active constituents of liquorice. Studies have revealed that these compounds exert inhibitory effects on several viruses, including SARS-CoV-2. The main mechanisms of action of these compounds include inhibition of virus replication, direct inactivation of viruses, inhibition of inflammation mediated by HMGB1/TLR4, inhibition of β-chemokines, reduction in the binding of HMGB1 to DNA to weaken the activity of viruses, and inhibition of reactive oxygen species formation. We herein review the research progress on the antiviral effects of glycyrrhizin and its derivatives. In addition, we emphasise the significance of exploring unknown antiviral mechanisms, structural modifications, and drug combinations in future studies.